PENDIDIKAN ISLAM DAN KECERDASAN MAJEMUK (MULTI INTELLIGENCES) DI MADRASAH MU‘ALLIMAAT MUHAMMADIYAH YOGYAKARTA - Sutarman, Sutarman (Universitas Ahmad Dahlan, 2014)
Madrasah Mu?allimat Muhammadiyah Yogyakarta is one of Charitable Enterprises Muhammadiyah.It was established by KH. Ahmad Dahlan in Yogyakarta, who can not be forgotten his contribution. It is a modern education which clings to the authentic teachings of Islam, namely the Qur?an and Al-Hadith, the education and development of general science (SQ, EQ, and AQ) that all the scientific aspects of inter-connective ties. Before the Indonesia?s independence until today, Madrasah is already taking part in educating the nation that prints quality education of human resources in order to prepare a reliable and robust human resources in a comprehensive manner that an educational process of the students in the school, not only hard skills but also soft skills. In terms of hard skills, Muhammadiyah Mu?allimat Madrasah curriculum prepares students to compete with graduate school / madrasah in general in Indonesia by providing an adequate portion of the curriculum with the standard SNP, the Ministry of Religion and ISMUBA and adjust to the demands of the times. Mu?allimaat Madrasah Education in Yogyakarta Muhammadiyah has implemented an integrated curriculum-inter connective. According to Amin Abdullah, the curriculum-inter connective is the existence of an implementation approach to epistemology bayani, Irfani and Burhani. It means that in addition to the education teaches spiritual intelligence which is guided by al-Qur?an and al-Hadith (prophetic intelligence), aspects of emotional intelligence, adversity intelligence and general science are also taught.